The Role of the Taman Pendidikan Al-Qur’an Al-Ikhlas in Character Formation of Children in Mojo Wetan Village, Sragen - Saputra, Davinda Aziz Syifa Wicaksana Adi; Hafidz, Hafidz (Journal of Educational Sciences, 2025)
In the midst of increasing moral challenges faced by children today, early Islamic education plays a critical role in character development. This study aims to describe the role of the Taman Pendidikan Al-Qur’an (TPA) Al-Ikhlas in shaping children's character in Mojo Wetan Village, Sragen, and to identify supporting and inhibiting factors in this process. The formation of a strong and noble character is the main goal of early Islamic education. This study uses a phenomenological approach through field research methods, utilizing data collection techniques in the form of observation, in-depth interviews, and documentation. The research subjects included students, ustadz, and parents or guardians. The results show that TPA Al-Ikhlas not only functions as a center for learning the Quran, but also as an institution for character formation through the instilling of praiseworthy morals, routine religious activities, fostering daily manners, and role models. Supporting factors include the religious environment and active parental involvement, while inhibiting factors include the lack of role models at home and the negative influence of technology. This study concludes that collaboration between TPA, families, and the wider community is crucial in building a generation of Muslims with strong character and contributing positively to their environment.